Experimental study on improving operating conditions of wet cooling towers using various rib numbers of packing. (May 2016) - Shahali, Pooriya; Rahmati, Mehdi; Alavi, Seyed Rashid; Sedaghat, Ahmad
Highlights: Performance of WCT is experimentally studied by changing water flow rate, inlet water temperature, rib numbers and air flow rate. Efficiency is in a direct relation with the inlet water temperature, rib numbers and air flow rate. Efficiency decreases through enhancing the water flow rate. Mathematical equations are derived by regression analysis of the measured data. A guideline is proposed to reach optimum operating conditions of WCTs. Abstract: There are different mass and heat transfer mechanisms between water and air flows inside wet cooling towers (WCTs) so that it is a very difficult task to manage or optimize their operations. In this experimental work, the WCT performance is parametrically investigated in order to understand effects of water flow rate, inlet water temperature, type and arrangement of packing, and mass flow rate of air. Three different types of PVC packings (7, 9 and 18 ribs) are studied in this article separately to investigate influences of rib numbers. Furthermore, operation of the WCT is investigated by changing the inlet water temperature, rib numbers of packing, and flow rate of air and water. Ultimately, a guideline is proposed to reach optimum operating conditions of WCTs by virtue of mathematical equations derived from regression analysis of the measured data.